Reliability and validity of predicted performance in the severe-intensity domain from the 3-minute all-out running test - Busso, T.; Lloria-Varella, J.; Sabater-Pastor, F. (International Journal of Sports Physiology and Performance, 2024)
Purpose The aim of this study was to analyze the reliability and validity of the predicted distance-time relationship in the severe-intensity domain from a 3-minute all-out running test (3MT).